Radicalization of Zaydi Reform Attempts - Shuja al Deen, Maysaa (AUC Knowledge Fountain, 2016)
This thesis is studying the development of the Zaydi doctrine in order to understand the reasons of emerging the Zaydi radical group, the Houthis. The studies about Zaydism are few, since it is a doctrine that only exists in Yemen, so it is considered a doctrine of a minor group. The studies about the contemporary Zaydism are much fewer, which leads to misunderstand the Houthi phenomenon. Zaydism has a long history in Yemen and the Zaydi Imamate controlled Yemen or the northern parts of Yemen for hundreds years. Therefore, the overthrow of the Imamate in 1962 and the establishment of t republican system were the biggest challenges that Zaydism has ever faced, since the Zaydi Imamate political theory is the main theme of the Zaydi doctrine. This thesis will demonstrate the main features of Zaydism; its main theological aspects and Social dimensions to study the contemporary Zaydism since the nineteenth century, when it shifted from a revolutionary doctrine of rebelled tribes to a state’s doctrine. Then, it will deal with the last period of the Imamate during the twentieth century and its collapse in 1962. The establishment of the republican system resulted profound outcomes on the Zaydi doctrine. After almost three decades of the republican revolution, the Zaydi revival groups emerged and established the Zaydi political parties and the Zaydi clubs to teach the Zaydi youth the Zaydi doctrine; all of these changes will be examinedin the thesis. These different phases that Zaydism passed through led to emerge the Houthi group. The reasons of emerging the Houthis group and the shift from a Zaydi revivalist movement to a radical one will be also discussed in this thesis.